Early heart rate responses to standardized trauma-related pictures predict posttraumatic stress disorder: a prospective study. - Suendermann, O; Ehlers, A; Boellinghaus, I; Gamer, M; Glucksman, E (2010)
OBJECTIVE: To investigate whether chronic posttraumatic stress disorder can be predicted by heart rate responses (HRR) and skin conductance responses (SCR) to standardized trauma-related pictures at 1 month after trauma has ocurred. Trauma survivors with PTSD report heightened physiological responses to a wide range of stimuli. It has been suggested that associative learning and stimulus generalization play a key role in the development of these symptoms. Some studies have found that trauma survivors with PTSD show greater physiological responses to individualized trauma reminders in the initial weeks after trauma than those without PTSD. METHODS: Survivors of motor vehicle accidents or physical assaults (n = 166) watched standardized trauma-related, generally threatening, and neutral pictures at 1 month post trauma, as their HRR and SCR were recorded. PTSD symptoms were assessed with structured clinical interviews at 1 month and 6 months; self-reports of fear responses and dissociation during trauma were obtained soon after the trauma. RESULTS: At 1 month, trauma survivors with PTSD showed greater HRR to trauma-related pictures than those without PTSD, but not to general threat or neutral pictures. HRR to trauma-related pictures predicted PTSD severity at 1 month and 6 months, and were related to fear and dissociation during trauma. SCR were not related to PTSD. CONCLUSION: HRR to standardized trauma reminders at 1 month after the trauma differentiate between trauma survivors with and without PTSD, and predict chronic PTSD. RESULTS are consistent with a role of associative learning in PTSD and suggest that early stimulus generalization may be an indicator of risk for chronic PTSD.